The effects of frenotomy on breastfeeding - MARTINELLI, Roberta Lopes de Castro; MARCHESAN, Irene Queiroz; GUSMÃO, Reinaldo Jordão; HONÓRIO, Heitor Marques; BERRETIN-FELIX, Giédre (Journal of Applied Oral Science, 2015)
Although the interference of tongue-tie with breastfeeding is a controversial subject, The use of lingual frenotomy has been widely indicated by health professionals. Objective : To observe changes in breastfeeding patterns after lingual frenotomy concerning the number of sucks, pause length between groups of sucking and mother's complaints. Material and Methods : Oral yes/no questions about breastfeeding symptoms and sucking/swallowing/breathing coordination were answered by the mothers of 109, 30 day old infants. On the same day the infants had their lingual frenulum assessed by administering a lingual frenulum protocol. After the assessment, all tongue-tied infants were referred for frenotomy; nevertheless, only 14 underwent the surgery. Of the 109 infants, 14 infants who did not have frenulum alterations were included as controls. Birth order and gender were the criteria for recruiting the control group. The tongue-tied infants underwent lingual frenotomy at 45 days of age. At the conclusion of the frenotomy, the infants were breastfed. At 75 days old, both groups – control and post-frenotomy – were reassessed. Before the reassessment the same oral yes/no questions were answered by the mothers of the 14 infants who underwent frenotomy. The mothers of the control group answered the questionnaire only at the time of the first assessment. Data were subjected to statistical analysis. Results : After frenotomy, the number of sucks increased and the pause length between sucking decreased during breastfeeding. The controls maintained the same patterns observed in the first assessment. From the questionnaire answered by the mothers of the 14 tongue-tied infants, at 30 days and 75 days, we observed that the symptoms concerning breastfeeding and sucking/swallowing/breathing coordination were improved after lingual frenotomy Conclusions : after lingual frenotomy, changes were observed in the breastfeeding patterns of the the tongue-tied infants while the control group maintained the same patterns. Moreover, all symptoms reported by the mothers of the tongue-tied infants had improved after frenotomy.